Adjunctive role of Q10 with Ligilactobacillus salivarius, and Lactiplantibacillus plantarum probiotic Bacteria on the HEp-2 cells viability and adhesion of Streptococcus mutans - Khodaii, Zohreh; Mardi, Shayan; Mardi, Parham; Natanzi, Mahboobeh Mehrabani (Frontiers in Cellular and Infection Microbiology, 2023)
Objective Various studies have indicated the application of Coenzyme Q10 and probiotic bacteria such as Ligilactobacillus salivarius (L. salivarius) and Lactiplantibacillus plantarum (L. plantarum) in combating periodontal disease. Considering the positive effect of these two on oral health, and the destructive effect of S. mutans, in this study, we investigate the outcomes of the administration of probiotics and Q10 on infected HEp-2 cell viability and S. mutans adhesion in different settings. Methods A 3-week-old human epidermoid laryngeal (HEp-2) cell line was cultured and exposed to two different probiotics and 3 different doses of Q10 doses. Samples were contaminated by S. mutans immediately (therapeutic setting) and after 3 hours (preventive setting). Eventually, the viability of HEp-2 cells was investigated by MTT. Also, the number of adhered S. mutans was explored by direct and indirect adhesion assays. Results L. plantarum and L. salivarius protect epithelial cells against S. mutans in both therapeutic and preventive settings, albeit not fully. In contrast, Q10 completely preserves the viability of infected Her HEp-2 cells at all concentrations. The effects of the coexistence of Q10 and probiotics were not quite equal, among which L. salivarius and 5 μg of Q10 form the best results. The microscopic adherence assay of S. mutans revealed that samples containing Q10 had significantly lower adhesion of probiotics and S. mutans to HEp-2 cells. Similarly, plates containing L. salivarius with 5μg or L. plantarum with 1μg Q10 or sole presence of L. salivarius had the lowest S. mutans adherence among others. Also, L. salivarius with 5μg Q10 had one of the highest probiotic adherences. Conclusion In conclusion, co-administration of Q10 and probiotics especially in presence of L. salivarius with 5μg Q10 could have remarkable effects on HEp-2 cell viability, S. mutans, and probiotic adherence. Nevertheless, our study, for the first time, showed that Q10 might have an anti-bacterial activity by suppressing the adhesion of tested bacteria to HEp-2 cells. This hypothesis, if correct, suggests that due to their different mechanisms, co-prescription of Q10 and probiotics may lead to better clinical responses, especially in the mentiond dose.